New blockchain consensus algorithm applied on healthcare industry: Proof of Visit- (POV) - Çetin Şahin; Muhammed Ali Aydin; Ahmet Sertbaş (Engineering Science and Technology, an International Journal)
The increase in the world’s population, technological advancements, genetic research, digital health services, and medical devices are among the reasons that lead to the rapid growth of Electronic Health Record (EHR). Health services, clinical studies, public health studies, health insurance data, health research, and similar sources generate a large amount of EHR. One of today’s important issues is the storage of data in centralized database systems and the fact that data accuracy and security are only ensured through these centers. Due to communication and integration issues between these centers, vital data such as examinations and laboratory tests can be repeated due to difficulty accessing the EHR. As citizens do not have full control over sharing their own EHR, this situation can cause deficiencies and disruptions in the healthcare process. Sharing personal EHR without the citizen’s consent can lead to data privacy issues. In systems where patient data is centrally stored, software changes can cause problems such as loss of patient data. The fact that the patient’s potentially valuable EHR is secondary causes irregular maintenance of the data. With its decentralized architecture and verification mechanisms, blockchain technology can work more efficiently than centralized structures without data loss or security problems. In this study, it is proposed to share EHR using blockchain infrastructure and to prepare a consensus algorithm specifically for health data on the blockchain. This way, personal EHR is stored in the patient’s own control and their own health wallet.